Delighting Consumers Click by Click: Antecedents and Effects of Delight Online. (August 2013) - Bartl, Christopher; Gouthier, Matthias H. J.; Lenker, Markus
The increasing importance of information technology as a means to access and communicate information has prompted firms to enhance their corporate websites to establish relationships with potential and current customers. Likewise, the value of satisfaction has decreased in favor of customer delight. To develop innovative and delighting websites, however, firms require a more detailed understanding of how they can optimize their websites' user impact. In two empirical studies, this research shows that delight has a stronger impact on purchase intentions than website satisfaction does. This means that companies can benefit from positive repercussions after investing up front to enhance their website. This research also identifies individual website quality factors that firms can manipulate to create delightful consumer web experiences. By examining and distinguishing between their effects on delight and surprise, this research sheds light on how consumers perceive website quality factors. Overall, this research shows how firms can attain customer delight in an online environment and clarifies its effects on consumer behavior.